Determination of Phenolic Compounds Levels and The Antioxidant Activity in Some Locally used spices - اسماعيل, مها; زينب صارم (Latakia University Journal -Medical Sciences Series, 2024)
Spices are a rich source of phenolic compounds with antioxidant activity. In this study, three types of spices were selected to determine their phenolic compound content and their antioxidant activity: cumin (Cuminum cyminum), coriander (Coriandrum sativum L.) and ginger (Zingiber oﬃcinale). The total content of phenolic compounds in the aqueous extract of each type of spice was determined using the reference Folin-Ciocalteau method. The antioxidant activity of the aqueous extracts of these spices was evaluated by the Reducing Power method, using vitamin C as a positive control. The aqueous extract of cumin showed the highest content of phenolic compounds, followed by the aqueous extract of ginger, while the aqueous extract of coriander showed the lowest content of phenolic compounds. The antioxidant activity of the aqueous extract of cumin was the highest among the studied spices, followed by the aqueous extract of coriander, while the aqueous extract of ginger was the lowest. The aqueous extracts of the studied spices were less effective as antioxidants compared to 100 mg of vitamin C.